The relationship between the bishop and the cathedral chapter in light of institutional changes in the communal era: Two examples from the Istrian Peninsula - Jenko Kovačič, Ana (En la España Medieval, 2022)
The second half of the 12th and the 13th century witnessed great institutional changes in Istrian towns due to the formation of communal government. This process, well-known in the Italian environment, included a certain degree of conflicts of interest with the local bishops. Two examples from Istria, namely the cities of Trieste and Poreč (Parenzo), lend themselves to interesting research. The bishops of Trieste, who held the public authority within the city walls from the mid-10th century onwards, presented a direct obstacle to the commune on its way towards complete autonomy. On the other hand, the bishops in Poreč understood the territory of the city district as the bishopric’s property. Their aspirations, which were based on the forged Privilegium Eufrasianum, also included fiscal and juridical powers and thus posed a problem for the communal development. Communes finally overcame both specific local situations; however, it is interesting to note that the reactions of the cathedral chapters differed greatly. Members of the chapter in Poreč stood by the bishop in his fight against the commune, which was backed by the power of Venice. Their counterparts in Trieste, though not so actively involved in the shift of the public power in the city, can eventually be regarded as the commune’s allies. The reasons for such different responses can be found not only in the practical, financial aspects, but also in the different relations within the bishopric in the previous centuries. Although cathedral chapters were not directly involved in the conflict and in the institutional changes per se, research into the relationship between chapters and bishops can provide an insight into bishoprics’ internal mechanisms that set the foundations for the late medieval and early modern period.